KEKRISTENAN DAN NASIONALISME DI KOTA BOGOR - Kustini Kustini; Syaiful Arif (Harmoni, 2016)
This study aims at exploring the perspective of the Christians in regard to some aspects namely nationalism, Indonesia constitution (Pancasila) and plurality or locally called Bhinneka Tunggal Ika. This study was conducted in five churches located in Bogor city. The research findings show that the Christians understand nationalism in the humanistic light of nationalism that place humanism as the aim of nation building. In relation to Pancasila, the Christian faith cannot be mixed with Pancasila. But Pancasila in itself contains the Christian values. The Christian values have to become the guidance for the church community in implementing Pancasila. In regard to plurality, the church can be equated as a medium of plurality making. The church programs are designed as such in support of plurality development. The research findings recommend that there is a need to construct the ideas of Indonesian Christianity so that it is not just seen as a slogan.